Les conflits fonciers comme analyseurs des guerres civiles : chefs de guerre, militaires américains et juges Taliban dans la Kunar - Adam Baczko (Revue des Mondes Musulmans et de la Méditerranée)
Land disputes are a particularly relevant point of entry to illuminate the political dynamics in Kunar. Consideration of conflicts over inheritance and plot demarcations constitute a particularly powerful means of analyzing the social tensions that fuel the civil war in this rural province of Afghanistan. The multiplication and politicization of land disputes throughout the last three decades highlight the dislocation of the political structures and the normative framework which regulated these conflicts before the Soviet invasion. Moreover, a comparison between the modes of regulating land disputes pursued by local commanders, the US military and the Taliban underlines the differences between three ways of governing people. In dealing with land disputes, political actors act directly on social relations, with decisive implications for their struggle against each other. An analysis of the war through the study of land conflicts helps us to more fully understand why the warlords are currently getting weaker, why the people of Kunar are rejecting the US Army, and why the Taliban movement has taken root locally.